Cultural factors of network inter-firm cooperation. Issue 2 (3rd June 2019) - Popov, Evgeny; Stoffers, Jol; Simonova, Victoria
Abstract : Purpose: The purpose of this study is to specify cultural properties that influence inter-firm cooperation, advancing a conventional theoretical economic-based framework. Design/methodology/approach: An evaluation of concepts related to parametric cultural assessment was the theoretical foundation for structural aspects of inter-firm collaboration, documented in an empirical study that investigates cross-cultural analysis. This study was based on research at a cross-national level, allowing cultural disparities to be captured. Therefore, the empirical basis was the sixth World Values Survey, which is the largest cross-national project for assessment of cultural values. Findings: It was found that cultural properties, as freedom of choice; advancement of norms for equal dissemination of power; low perceived uncertainty; strategic orientation on the future; and spread norms of humanistic orientation would further develop inter-firm cooperation. Practical implications: The current study specifies a systematic and practical definition of attributes in the culture of inter-firm collaboration. Advantages of such advanced frameworks are more sustainable collaboration models, decreased expenses of inter-firm coordination methods and possibilities for establishing network knowledge among collaborating firms – a necessity for competitive advantage in today's global economy. Originality/value: To the best of the authors' knowledge, no previous research has been undertaken that specifies cultural properties influencing inter-firm cooperation, advancing a conventional theoretical economic-based framework.